Hippodonta fujiannensis sp. nov. (Bacillariophyceae), a new epipsammic diatom from the low intertidal zone, Fujian Province, China - Zhao, Long; Sun, Jiandong; Gao, Yahui; Liang, Junrong; Sun, Lin; Li, Xuesong; Chen, Changping (Phytotaxa, 2017)
Hippodonta fujiannensis sp. nov., a new small-sized species of Hippodonta (Bacillariophyceae), was described from the low intertidal zone, Fujian Province, China. The morphology and ultrastructure were investigated by light and scanning electron microscopy, which revealed the following results: 1) valves asymmetrical, elliptic-lanceolate to rhombic-lanceolate with non-protracted apices; 2) raphe filiform, with teardrop-shaped and closely spaced central endings; 3) striae uniseriate, evenly spaced throughout the whole valve; 4) single row of lineolae around the valve apices. In particular, this new species is characterized by its dissymmetrical valves with one special column of lineolae which is close to the raphe and positioned perpendicular to the remaining lineolae of the striae, on only one side of the valves. Hippodonta fujiannensis is epipsammic and inhabits the marine environment. Conventional morphometric analyses were employed to elucidate the differences between this new species and several taxa similar in valve morphology, and the results are discussed.